Cost-Effectiveness of Pertussis Vaccination During Pregnancy in the United States - Atkins, Katherine E. (Am J Epidemiol, 2016)
Vaccination against pertussis has reduced the disease burden dramatically, but the most severe cases and almost all fatalities occur in infants too young to be vaccinated. Recent epidemiologic evidence suggests that targeted vaccination of mothers during pregnancy can reduce pertussis incidence in their infants. To evaluate the cost-effectiveness of antepartum maternal vaccination in the United States, we created an age-stratified transmission model, incorporating empirical data on US contact patterns and explicitly modeling parent-infant exposure. Antepartum maternal vaccination incurs costs of $114,000 (95% prediction interval: 82,000, 183,000) per quality-adjusted life-year, in comparison with the strategy of no adult vaccination, and is cost-effective in the United States according to World Health Organization criteria. By contrast, vaccinating a second parent is not cost-effective, and vaccination of either parent postpartum is strongly dominated by antepartum maternal vaccination. Nonetheless, postpartum vaccination of mothers who were not vaccinated antepartum improves upon the current recommendation of untargeted adult vaccination. Additionally, the temporary direct protection of the infant due to maternal antibody transfer has efficacy for infants comparable to that conferred to toddlers by the full primary vaccination series. Efficient protection against pertussis for infants begins before birth. We highly recommend antepartum vaccination for as many US mothers as possible.